Desain dan Analisis Struktur Variasi Paddock Motor Menggunakan Metode Elemen Hingga - Alda, Ragil; Agung Ariesta, Igan; Riza Aditya, Sena; Nurwimbo, Fani; Bagus Prasetiyo, Angger (Retii, 2023)
One other central support that is used in motor sports is the paddock stand. Increased need for shipyards is a result of Indonesia's growing motorsports industry. A decent stand must be ideal in terms of material, design, and size in addition to being appropriate for motorcycle installation. Finite elements were used in this study's static analysis to establish the distribution of total deformation, stress, and safety factor under a loading of 2000 N. According to the investigation, the second paddock stand design variant has greater equivalent stress and total deformation values with values of 375.83 MPa and 0.54331 mm. The paddock stand design is still not safe for 2000 N loads, according to the safety factor value